New methods for thalassemia screening: TGA/Chemometrics test is not influenced by the aging of blood samples - Risoluti, Roberta; Caprari, Patrizia; Gullifa, Giuseppina; Massimi, Sara; Sorrentino, Francesco; Buiarelli, Francesca; Materazzi, Stefano (Microchemical journal, 2019)
The coupling of Thermogravimetry (TG) in conjuction with chemometrics was investigated for the first time to evaluate the capabilities of this novel test to provide the screening of thalassemia in blood samples stored at 4 °C until 15 days. Healthy donors were considered as reference subjects and a typical thermal behaviour as a function of aging was estimated and compared to thermal behaviour of thalassemia subjects. Diagnosis of thalassemia was made at the Day-Hospital Thalassemia of S. Eugenio Hospital through a comprehensive assessment of clinical presentation and hematological and molecular analysis. Despite blood changes with aging, the application of the TGA/Chemometrics test reveal that healthy and thalassemic population may be significantly differentiated after 15 days from blood collection with a 100% of correct classification rate. This new method applied to aged samples was able to discriminate thalassemia in transfused patients that is generally not possible by the common first level protocol used for thalassemia screening, and in δβ-thalassemias, and β-thalassemia combined with Hb Lepore, usually requiring the molecular analysis for diagnosis. This study, for the first time, describes a screening method for thalassemia able to detect thalassemia on whole blood samples stored for 15 days. In conclusion TGA/Chemometrics screening test for thalassemia is not influenced by the aging of blood samples and this approach could open the way to prevention programs for thalassemia also in the developing countries where expertise and facilities for their control are extremely limited or in situation involving delayed analyses. [Display omitted] •TGA/Chemometrics is able to detect Thalassemia on whole blood samples stored for 15 days.•New screening programs for Thalassemia in developping countries with high frequency involving delayed analyses.•Collection and sending blood samples for timely and accurate diagnosis.